UV-light-induced curing of branched epoxy novolac resin for coatings - S. Gaidukovs; A. Medvids; P. Onufrijevs; L. Grase (eXPRESS Polymer Letters)
UV-light induced curing of the branched epoxy novolac resin (ENR) is reported. Cross-linked ENR coatings with a thickness of 150 µm were produced by the cationic photopolymerization of poly((phenyl glycidyl ether)-co-formaldehyde), which was photoinitiated by bis(4-dodecylphenyl)-iodonium hexaflurorantimonate. ENR crosslinking efficiency of UVlight polymerization accomplished by Hg-lamp with a power of 1 kW continuous irradiation was investigated as a function of the photoinitiator content and UV curing time. Optimal cross-linking properties were observed for photoinitiator concentration of 1.5%, and curing time 5 min. It was found that higher Vickers hardness of the polymer resulted in an increased cross-linking density of the developed chain network. UV irradiation time longer than 6 min results in the photodegradation of the polymer. This was confirmed by scanning electron microscopy investigations of polymer surface microstructure, as well as complemented by Fourier transform infrared (FTIR), ultraviolet-visible (UV-VIS) and Raman spectroscopy measurements that evidence the oxygen containing groups. Furthermore, the developed ENR photopolymerization technology can be used to obtain protective coatings for applications in power generation and maritime industries where thermal curing processes and two-component resin hardening are unacceptable.